THE IMPACT OF SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE ON ANXIETY LEVELS IN PRE-OPERATIVE REGIONAL ANESTHESIA PATIENTS AT RSUD BENDAN PEKALONGAN. - Safira Lamangantjo; Muhaji; Vita Purnamasari (Keperawatan Anestesiologi Program Sarjana Terapan, 2025)
Background: Pre-operative anxiety is a psychological condition frequently experienced by patients before undergoing surgical procedures, particularly with regional anesthesia techniques. Unmanaged anxiety can affect the physiological condition of patients and disrupt the surgical process. One effective non-pharmacological intervention for reducing anxiety is the Spiritual Emotional Freedom Technique (SEFT).Methods: This research employed a quasi-experimental method with a two-group pretest-posttest design. A total of 30 respondents were divided into two groups: 15 respondents in the experimental group receiving SEFT intervention and 15 respondents in the control group. The sampling technique used was consecutive sampling. Data collection instruments included the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire. Data analysis was conducted using the Wilcoxon test.Results: The results indicate a significant reduction in anxiety levels in the experimental group after receiving SEFT intervention, with a p-value of 0.001 (p < 0.05). In contrast, the control group showed no significant changes.Conclusion: This study concludes that SEFT therapy is effective in reducing anxiety levels in pre-operative regional anesthesia patients